Critical assessment of support for the evolution of photovoltaics and feed-in tariff(s) in Italy. (March 2015) - Di Dio, V.; Favuzza, S.; La Cascia, D.; Massaro, F.; Zizzo, G.
Abstract: The feed-in tariff(s) mechanism involves an obligation on the part of an electricity provider to purchase electricity generated by renewable energy sources in its relevant area, paying a tariff determined by public authorities and guaranteed for a specific time period. Feed-in tariff(s) have been the primary mechanism used for supporting the development of renewable energy sources in the EU and, up to date, they are being applied in 20 EU Member Countries. On 6 July 2013, the Italian experience with feed-in tariff(s) for photovoltaic systems finished. During its lifetime of eight years, this incentive mechanism, named "Conto Energia", was characterized by periods of great success followed by others of serious skepticism. The implementation of the Italian feed-in tariff(s) mechanism was changed many times, becoming very close to the European standard.